(untitled) (Revista Internacional de Formação de Professores, 2019)
The aim of this paper is to discuss the results of a research about of difficulties in Physics teaching. For that, a narrative inquiry was done with Sciences teachers of a middle school of Uberlândia, Minas Gerais, Brazil. The research data were collected through interviews, memorials and documents. The results showed that the main difficulties of the teachers about Physics teaching are in domain of contents, teaching methodology and mathematics language.